Role of Entrepreneurship in Economic Growth of Nepal - Karki, Nirajan; Bista, Nar Bahadur (Nepalese Journal of Finance, 2025)
This study examines the role of entrepreneurship in economic growth of Nepal. Economic growth is the dependent variable. The selected independent variables are infrastructure development, market condition, access to capital, education skills, and innovation and technology. The primary source of data is used to assess the opinions of respondents regarding infrastructure development, market condition, access to capital, education skills, innovation and technology, and economic growth. The study is based on primary data of 126 respondents. To achieve the purpose of the study, structured questionnaire is prepared. The correlation and multiple regression models are estimated to test the significance and importance of role of entrepreneurship in economic growth of Nepal. The study showed a positive impact of infrastructure development on economic growth. It indicates that development in infrastructure leads to increase in economic growth. Similarly, the study showed a positive impact of market condition on economic growth. It indicates that h increase in external economic environment leads to increase in economic growth. Likewise, the study also revealed a positive impact of access to capital on economic growth. It indicates that effective utilization and mobilization of money leads to increase in economic growth. Further, the study observed a positive impact of education skills on economic growth. It indicates that higher the educational skills related to entrepreneur, higher would be economic growth. In addition, the study observed a positive impact of innovation and technology on economic growth. It indicates that use of innovative technology leads to increase in economic growth.